Experiments in physics education: Where do Czech teachers get inspired? - Marounová, Jana; Kácovský, Petr (Scientia in educatione, 2023)
The main aim of this study, which is part of a large research concerning the role of experiment in physics teaching and learning, is to map the sources of inspiration for experimental activities used by Czech upper secondary school physics teachers in their lessons. To achieve this goal, an online questionnaire has been sent in November 2020 to physics teachers at both general and specialized upper secondary schools. 309 of the nearly two thousand recipients have provided their answers. After evaluating two selected questions from the questionnaire, it was discovered that the most significant source of inspiration for teachers in most age groups is the Internet, with the only exception being the eldest teachers with more than thirty-year work experience who prefer printed collections and textbooks. Among male physics teachers there is almost twice the percentage of those who claim to use some experiments of their own design compared to female physics teachers. Large differences when choosing the source of inspiration can be found based on the type of school at which the teacher works. Teachers from general schools use as inspiration printed sources and their own colleagues significantly more than their counterparts from specialized schools.